Contrasting genetic structure in Plasmodium vivax populations from Asia and South America. - Imwong, M; Nair, S; Pukrittayakamee, S; Sudimack, D; Williams, J; Mayxay, M; Newton, P; Kim, JR; Nandy, A; Osorio, L; Carlton, J; White, N; et al. (2007)
Populations of Plasmodium falciparum show striking differences in linkage disequilibrium, population differentiation and diversity, but only fragmentary data exists on the genetic structure of Plasmodium vivax. We genotyped nine tandem repeat loci bearing 2-8 bp motifs from 345 P. vivax infections collected from three Asian countries and from five locations in Colombia. We observed 9-37 alleles per locus and high diversity (He=0.72-0.79, mean=0.75) in all countries. Numbers of multiple clone infections varied considerably: these were rare in Colombia and India, but > 60% of isolates carried multiple alleles in at least one locus in Thailand and Laos. However, only one or two of the nine loci show >1 allele in many samples, suggesting that mutation within infections may result in overestimation of true multiple carriage rates. Identical nine-locus genotypes were frequently found in Colombian populations, contributing to strong linkage disequilibrium. These identical genotypes were strongly clustered in time, consistent with epidemic transmission of clones and subsequent breakdown of allelic associations, suggesting high rates of inbreeding and low effective recombination rates in this country. In contrast, identical genotypes were rare and loci were randomly associated in all three Asian populations, consistent with higher rates of outcrossing and recombination. We observed low but significant differentiation between different Asian countries (standardized FST = 0.13-0.45). In comparison, we see greater differentiation between collection locations within Colombia (standardized FST = 0.4-0.7), and strong differentiation between continents (standardized FST = 0.48-0.79). The observed heterogeneity in multiple clone carriage rates, linkage disequilibrium and population differentiation are similar in some, but not all, respects to those observed in P. falciparum, and have important implications for the design of association mapping studies, and interpretation of P. vivax epidemiology.